Marginality Phenomena and New Uses on the Agricultural Land. Diachronic and Spatial Analyses of the Molise Coastal Area - Cialdea, Donatella; Mastronardi, Luigi (TeMA - Journal of Land Use, Mobility and Environment, 2014)
This paper analyzes the evolution of land use in the Molise Region. The attention is focused on the changes that occurred primarily on the rural area of the coastal area in this Region. The presence of urban centers of limited dimension, both for the demographic performance and for the dimensional order, is the main characteristic of this area. The historic part of rural tradition, at the same time, no longer emerges as a primary component of the regional landscape. This trend is particularly evident in the coastal zone, which is analyzed in this work not only in the range of areas that directly bordering the Adriatic Sea, but also in its pre-coastal zone, which remains imprinted on a matrix rural, but suffering from marginalization phenomena